Coastalplain Honeycombhead, Balduina angustifolia - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS)
Coastalplain honeycombhead is found in beach dunes, coastal grasslands, and scrub throughout Florida and into Alabama and Mississippi. It is a prolific flower and seed producer that attracts numerous pollinators, including the gulf fritillary butterfly. Interestingly, the endemic, solitary, and ground-dwelling coastal plain Hesperapis (Hesperapis oraria), also known as Balduina bee, is completely dependent on the coastalplain honeycombhead for survival, only emerging from the ground a few weeks each year in September to October to collect pollen and nectar (Hunsburger 2013). This bee only occurs on barrier islands and peninsulas in the northern Gulf of Mexico (Hunsburger 2013) and is particularly vulnerable to climate-change-driven sea-level rise and habitat fragmentation. https://edis.ifas.ufl.edu/sg163